Discussing Sex in Marriage: How Married People Maintain Intimacy During Pandemic - Novianti, Wiwik; Setiansah, Mite; ., Nuryanti (KnE Social Sciences, 2023)
Studies on sexual communication are rare in Indonesia. Talking about sex is not easy for Indonesians, especially Javanese, to do. Sex is something sacred and taboo to talk about. So for many people, sex only needs to be done but does not need to be discussed, even with their partners. Couples spend more time together during the pandemic, but data shows that divorce rates are increasing. This qualitative study aims to understand the verbal communication used by married couples when they talk about sex and the implications for intimacy among them. The data were collected using semi-structured interviews with ten married couples in Banyumas, Central Java. The data were analyzed using a phenomenological approach. Four major themes emerged: Sex as a necessity, sex as an obligation, the choice of contraceptives, and Banyumas culture as a reference in marriage. From the research, it was found that talking about sexuality in marriage increasing intimacy with the spouse and also fostered feelings of being valued by the spouse. Keywords: qualitative study, marriage, sexuality, intimacy, verbal communication